Evaluasi Kinerja Manajemen Dan Keuangan Pemerintah Kota Surabaya Tahun Anggaran 2020 - 2022 - Madaniyah, Riza Nur; Widiasih, Suprapti (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
This research aims to provide an overview the financial performance of the City of Surabaya for the 2020 - 2022 budget year, so that the Surabaya City is expected to be able to increase and maximize local revenue and be able to immediately take preventative action if it experiences an economic crisis. This research uses quantitative descriptive methods. The data collection technique used was observation of the Surabaya City Regional Government Financial Report. The data used in this research is secondary data sourced from the Surabaya City Government Budget Realization Report for 2020 - 2022. The analytical technique used in this research is financial ratio analysis such as: the ratio of the effectiveness of regional original income, the ratio of regional financial independence, the ratio of the degree of fiscal decentralization, and the ratio of spending harmony. Based on the results of data processing and discussion, it shows that the financial performance of the Surabaya City Government for the 2020 - 2022 budget year when viewed from the Effectiveness Ratio of Local Own Revenue is 86.05% with the category ineffective, Then from the average of independence ratio is 152.37% and is in the delegative category, which means that the Surabaya City Government is not dependent on central government assistance funds, the average of Fiscal Decentralization ratio is 58.03%, which is in the very good category and the average Operational Expenditure Ratio was 82.68% while the Capital Expenditure Ratio was 20.97%.